Pharmacoinformatics study of Piperolactam A from Piper betle root as new lead for non steroidal anti fertility drug development. (April 2017) - Amin, Sk. Abdul; Bhattacharya, Plaban; Basak, Souvik; Gayen, Shovanlal; Nandy, Ashis; Saha, Achintya
Graphical abstract: Highlights: The manuscript suggests finding of a new non-steroidal contraceptive agent. The non-steroidal contraceptive lead is Piperolactam A (PLA), an aristolactam isolated from Piper betle Linn. PLA has more binding affinity towards estrogen and progesterone receptors than Rohitukine and Org C, standard antagonists to the receptors. The ADMET analysis revealed lower toxicity and a good score on therapeutic efficacy of the compound. Docking studies on mammalian hERG and Cytochrome P450 protein suggests poor binding thus low cardiac and liver toxicity of the compound. Abstract: Fertility control is a burning problem all over the world to regulate population overflow and maintain ecological balance. This study is an in-silico approach to explore a non-steroidal lead as contraceptive agent in order to avoid several contraindications generated by steroidal analogues. Piperolactam A, an aristolactam isolated from Piper betle Linn. showed binding affinity towards estrogen and progesterone receptor as −8.9 and −9.0 Kcal/mol (inhibition constant Ki = 0.294 μM and 0.249 μM) respectively which is even larger than that of reported antagonists such as Rohitukine and OrgC (binding affinity −8.7 and −8.4 Kcal/mol; Ki 0.443 μM and 0.685 μM respectively). The binding site exploration displayed more hydrogen bonding of Piperolactam A (His 524, Leu 346, Thr 347) than Rohitukine and OrgC (Leu 718) with associated receptors which was further confirmed by molecular dynamics simulations. The drug-likeliness of the compound has been proved from its tally with Lipinsky's Rule of Five and lowered toxicity such as cardiac toxicity, liver toxicity, mutagenicity and ecological toxicity. Endocrine disruptome and later docking guided molecular simulations revealed that Piperolactam A has weaker binding affinity and/or lower probability of binding with nuclear receptors especially hERG and cytochrome P450. The high Caco-2 permeability suggested more bioavailability hence more therapeutic efficacy of the drug.